Mathematical Modeling of Power Supply of an Autonomic Enterprise Based on Wind Power Plants - Telegin, Valeri; Stepanov, Anatoli (International Journal of Engineering and Technology, 2018)
Power supply systems for small businesses based on renewable energy sources are most often based on converting wind energy, solar energy and water energy. Calculating its effectiveness is a time-consuming task, requiring the processing of a large amount of data specific for the geographical location of power generating units. In the article the technique of computer modeling of work of a park of wind power plants (WPP) with the purpose of definition of an optimum parity of their parameters is considered.Â Â